Parental Psychosocial Well-Being as a Predictor of the Social Competence of a Child - Panula Venla; Junttila Niina; Aromaa Minna; Rautava Päivi; Räihä Hannele (Springer Science and Business Media LLC, 2025)
Our study examined the interrelations between the psychosocial well-being of parents at the time of pregnancy and the social competence of their three-year-old child. Whereas most previous studies have linked the psychosocial well-being of one parent to the social development of their child, newer research has highlighted the importance of examining the psychosocial well-being of both parents and its’ effects to the development of the child. This study used data from the Steps to the Healthy Development and Well-being of Children follow-up study (The STEPS Study, n = 1075) to examine the interrelations between the psychosocial well-being of both the mother and the father during the period of pregnancy and the social competence of their three-year-old child. The interrelations between the psychosocial well-being of one parent and the social competence of their child were studied with regression analyses, and family-level interrelations were modeled with a latent profile analysis of family-level psychosocial well-being. At the dyadic level, the poorer psychosocial well-being of one parent during the pregnancy period mostly predicted poorer social competence in their child. However, at the family level, these links were not statistically significant. The higher level of psychosocial well-being experienced by one parent seemed to protect the development of the social competence of their child. This study emphasizes the need to consider the psychosocial well-being of both parents as a factor that influences the social development of their child.